Force-extension of the Amylose Polysaccharide - van den Berg, Rudolf (Department of Computer Science, 2014)
Myasthenia gravis (MG) is an autoimmune disorder in which auto-antibodies directed at the acetylcholine receptors (AChR) of the neuromuscular junction (NMJ) block, alter or destroy their targets. The anti-AChR antibodies cause activation of the classical complement pathway leading to inflammatory injury at the NMJ. Decay Accelerating Factor (DAF), a member of complement regulatory proteins, prevents activation of autologous components of complement pathways. The absence of DAF, in knock-out mouse models, has been shown to significantly increase the susceptibility to experimental autoimmune MG. A previous study showed that a high proportion of South African MG patients of African genetic ancestry develop immunosuppressive therapy-resistant extraocular muscle (EOM) dysfunction. We hypothesized that these patients have deficient DAF expression in their EOMs resulting in less protection from complement injury. Sequence analysis of relevant regions of the DAF gene revealed a single nucleotide polymorphism (SNP), c.-198C>G, in the promoter region in MG patients of African genetic ancestry with severe EOM MG involvement (MG n=101; Control n= 132; Odds ratio= 6.6; p=0.009). DAF-luciferase reporter assays, using 3 different cell lines (COS-7, HT1080 and C2C12) revealed that the c.-198C>G SNP (Mut-DAF) led to an increase in DAF promoter activity (